Evaluating the Impact of Infrastructure Rehabilitation Projects on Household Welfare in Rural Georgia - Lokshin, Michael; Yemtsov, Ruslan (World Bank, Washington, DC, 2014)
The authors evaluate the effect of various community level infrastructure rehabilitation projects undertaken in rural Georgia on household well-being. Their analysis is based on combining household and community level survey data. The authors' empirical approach uses the panel structure of the data to control for time-invariant un-observables at the community level by applying propensity-score-matched double difference comparison. The results indicate that improvements in school and road infrastructure produce nontrivial welfare gains for the poor at the village and country levels. The impact of water rehabilitation projects is ambiguous. School rehabilitation projects produce the largest gains for the poor. The methodological lesson from this analysis is that ad hoc community surveys matched with ongoing nationally representative surveys can provide a feasible and low cost impact evaluation tool.